PENGARUH RETURN ON ASSET, EARNING PER SHARE, DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM PADA PERUSAHAAN FARMASI (Periode 2013-2020) - Erlangga Ananda R; Faidatul Mukarromah; Lisa Lisa; Hanaa Hakim L (Nusantara Hasana Journal, 2023)
The share price is the price on the stock market for a certain period of time determined by market participants and is determined by the demand and supply of the shares concerned so that they change and create a new balance in the capital market. The stock price also reflects a company's value, the higher the value, the higher the stock price. The share price is an indicator of the successful management of the company, so that it also influences the increase in shareholder wealth. This research was conducted to determine the effect of Return On Assets, Earning Per Share, and Net Profit Margins on Stock Prices in pharmaceutical companies for the 2013-2020 period. The method used in this study is multiple linear regression, T-test and F-test, where before carrying out multiple linear tests, the classic assumption test is carried out first. The results of this study prove that the ROA, EPS and NPM variables partially have a significant effect on the stock prices of pharmaceutical companies. listed on the Indonesia Stock Exchange for the 2013-2020 period.